Numerical analysis of conjugate convection heat transfer in an open cavity with different phase change materials surrounded by plexiglass - Öztop, Hakan Fehmi; Selimefendigil, Fatih; Cosanay, Hakan; Abu-Hamdeh, Nidal (Taylor & Francis Inc, 2024)
Phase change (PC) process and convection inside an open cavity equipped with two different PCMs are analyzed with the finite volume method with ANSYS Fluent. The analysis is conducted for three different Grashof number (Gr) values for fully and partly open configurations. It is observed that the PC becomes fast when the object is closer to the exit for the fully open case. The partly open case results in higher thermal performance improvements while the average Nusselt number (Nu) increment is 94.5% for PCM-18. PC and heat transfer characteristics are influenced by both material and location of the PCM. At Gr = 3.79 x 10(8), the average Nu rises by about 50% when PCM-22 is used instead of PCM-18. Location and type of PCM provide excellent tool for controlling the phase transition and heat transfer dynamics with a fully and or partly open cavity.
Keywords: Finite volume method; heat transfer; material type; open cavity; PCM